Leveraging technology as a response to the COVID pandemic adapting diverse technologies, workflow, and processes to optimize integrated clinical management - Pappas, Harry; Frisch, Paul (Intelligent health series, 2022)
In 2019 the world was struck with the Coronavirus (COVID-19) infecting major portions of the world's population. There were no vaccines or treatments available to help mitigate the disease or offer a cure. The world's health systems were inundated with massive numbers of patients with varying ranges of symptoms, acuity, and levels of criticality. The world's healthcare organizations soon found themselves in an unmanageable situation, directly impacting the ability to manage patients across the entire healthcare environment. Most healthcare institutions had plans for emergency preparedness and procedures to deal with temporary crises, none of which were effective against the impact of COVID-19. COVID-19 was a highly contagious disease, resulting in high volumes of admissions with long lengths of stay. The virus quickly overwhelmed institutions with large patient volumes, resulting in shortages of patient beds, medical equipment, personal protective devices, cleaning agents, and other critical supplies. Hospital operations were further impacted by staff shortages due to exposure, resulting contagion, the shutdown of transit systems, and responsibilities at home due to school and business closures. This timely and important book describes the impact on the hospital ability to provide patient care and how healthcare institutions leveraged diverse technology solutions to combat the impact of COVID-19 on providing patient care. The authors also discuss implementation of these technology solutions and the many lessons learned of how healthcare institutions can enhance their emergency preparedness in the future from the COVID experience. The authors would like to acknowledge, thank, and dedicate this book to the hundreds of thousands of healthcare workers around the world who spent countless hours and put their own lives and families lives at risk to help patients though this pandemic.